ANALISIS PROSPEK PERKEMBANGAN MODAL DAN TENAGA KERJA PADA INDUSTRI KECIL DI KABUPATEN SIDENRENG RAPPANG - Agus Syam (Tasharruf: Journal Economics and Business of Islam, 2017)
Abstract Analysis of Prospect Capital Growth and Employment in Small Industries in The District Sidenreng Rappang. This research was conducted to answer the question "what are the prospects of capital growth and labor in the District Small Industries Sidenreng Rappang 5 (five) years from (2012-2016)". Thus, this study aims to determine how the prospect of the development of capital and labor in the District Small Industries Sidenreng Rappang 5 (five) years from (2012-2016). To that end, this study expected to be useful: (1) provide information for Local Government and the Department of Cooperatives and Small and Medium Enterprises in order to foster small-scale industries in the district Sidenreng Rappang, (2) as a reference material other researchers who study small-scale industries in the district Sidenreng Rappang. This research is a descriptive study using data time series (data year) only selected sub-populations in 2007-2011 for the development of capital and labor. Data collection techniques used are; documentation, interviews, and observations. Analysis of the data used, namely: qualitative and quantitative descriptive analysis. Result of research show the; 1) Capital developments in small industry in the District Sidenreng Rappang past five years (2007-2011) has increased by an average of 10.31 percent annually, 2) The development of labor in small-scale industries in the district Sidenreng Rappang past five years (2007-2011) has increased by an average of 1.04 percent annually, and 3) Development prospects of capital and labor in small-scale industries in the district Sidenreng Rappang for the coming five years (2012-2016) amounted to 3.93 percent.Kata Kunci: Modal, Tenaga Kerja dan Industri Kecil